Panorámica de la antropología de la educación en España: estado de la cuestión y recursos bibliográficos - Jociles, María Isabel (Revista de Antropología Social, 2007)
In this article there is reconstructed the history of the anthropology of the education in Spain, and the idea defends itself of that this one, in spite of the precedents who can be in previous decades, does not develop but from the 90, moment in which –besides– it begins to specialize in the study of the ethnic minorities. Like that, due –for a side– to the characteristics of the social and historical context associate in whom the sub-discipline is born in our country and –for other one– to the fact of which it takes the North American tradition as a precedent, the majority of the Spanish representatives of the anthropology of the education have not approached processes of transmitsión/acquisition of culture –as it wants the programmatical definition of the same one–, but phenomena related to the diversity and/or to the cultural minorities that –as it has been insinuated– have been identified exclusively by the diversity and/or the ethnic minorities or, more frequently, ethnic-national.